Synthesis and characterizations of degradable aliphatic-aromatic copolyesters from lactic acid, dimethyl terephthalate and diol: Effects of diol type and monomer feed ratio (eXPRESS Polymer Letters, 2010)
Lactic acid-based aliphatic/aromatic copolyesters are synthesized to incorporate the degradability of polylactic acid and good mechanical properties of aromatic species by using polycondensation of lactic acid (LA), dimethyl terephthalate (DMT), and various diols. Effects of diol lengths and comonomer feed ratios on structure and properties of the resulting copolymers are investigated. Three types of diols with different methylene lengths are employed, i.e., ethylene glycol (EG), 1,3-propanediol (PD) and 1,4-butanediol (BD). LA/DMT/diol feed ratios of 2:1:2, 1:1:2, and 1:2:4 are used in each diol system. It is found that types of the diols play an important role in the properties of the copolyester, where an increase in diol length results in an increase in the copolymers molecular weight, and a decrease in Tg, Tm and crystallinity, when a constant monomer feed ratio is employed. Monomer feed ratio also has a significant effect on properties of the copolymers, where an increase in the aromatic content leads to formation of copolymers with higher molecular weight, longer aromatic block sequence and high aromatic to aliphatic ratio in the chain structure. These, in turn, lead to an increase in Tg, Tm, crystallinity and thermal stability of the copolymer samples, and a reduction in their solubility.